Drug-induced lung disease: a brief update for radiologists - Furkan Ufuk; Selen Bayraktaroğlu; Ayşe Rüksan Ütebey (Diagnostic and Interventional Radiology, 2023)

(untitled)
Pulmonary adverse events and drug-induced lung disease (DILD) can occur when treating many conditions. The incidence of DILDs in clinical practice and the variety of radiological findings have increased, mainly due to the increased use of novel therapeutic agents. It is crucial to determine whether the newly emerging clinical and imaging findings in these patients are due to the progression of the underlying disease, infection, pulmonary edema, or drug use, as this will change the patient management. Although the diagnosis of DILD is usually obtained by excluding other possible causes, radiologists should be aware of the imaging findings of DILD. This article reviews the essential radiological results of DILD and summarizes the critical clinical and imaging findings with an emphasis on novel therapeutic agents.